Proceedings of 10th International Conference on Computer and Information Technology (ICCIT 2007), 27-29, December 2007, United International University, Dhanmondi, Dhaka-1209, Bangladesh organized by [Faculty of Science and Engineering], United International University. (School of Science and Engineering, United International University, 2007)
Contributed papers.